F22 An assessment of alcohol abuse on cognitive abilities, executive functions and motor signs in huntington's disease. (16th November 2010) - Irving, S; Milders, M; Simpson, S A
Abstract : Background: It has been acknowledged that high levels of alcohol use in Huntington's disease (HD) patients is associated with greater ratings of psychiatric symptoms, increased psychiatric symptom progression, and a younger age of HD symptom onset. However, there has been no research investigating the effects of alcohol abuse on the motor and cognitive signs/symptoms of HD and their rate of disease progression. Aim: The aim of this study is to investigate the role of alcohol abuse in the motor and cognitive signs and symptoms of HD. Methods: Using the data of 685 participants diagnosed with HD (58 current-abusers of alcohol) from the European Huntington's Disease Network (EHDN), it was hypothesised that alcohol abuse in HD will cause motor and cognitive signs/symptoms to progress faster and that alcohol abuse results in greater severity of illness. Results: A series of 3 X 2 repeated measures ANOVA's and a hierarchical regression revealed that current-abusers of alcohol had better motor functional ability and better cognitive ability than the non-abuser participants. Both of these effects remained across a three year period. The effect of alcohol on the severity of illness produced a trend, although non-significant, that indicated that alcohol does produce a negative effect on the progression of HD, with alcohol abusers progressing faster. Conclusions: Abusers of alcohol had better motor and cognitive abilities than non-abusers of alcohol. However, there is a likelihood that participants in the current-abuser group were at an earlier stage in the disease.